Akibat Hukum Peralihan Hak Atas Tanah Dalam Objek Sengketa - Mohammad Abdul Hakim Amrulloh (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the legal consequences of land rights transfer in disputed objects using a normative legal research method. Issues related to the transfer of land rights often give rise to legal disputes between interested parties, particularly when the transfer process does not comply with the prevailing agrarian laws and regulations. This research employs both the statutory approach and the conceptual approach to examine relevant legal provisions in depth, such as Law Number 5 of 1960 concerning the Basic Agrarian Principles (UUPA) and Government Regulation Number 24 of 1997 concerning Land Registration. The data were obtained from primary, secondary, and tertiary legal materials and analyzed qualitatively, emphasizing legal interpretation and expert doctrines. The findings reveal that any transfer of land rights carried out without proper legal procedures, both administratively and substantively, may result in legal consequences such as null and void transactions, ownership disputes, and even the annulment of land certificates by the court. Furthermore, it was found that the principles of legal certainty and legal protection for landowners are often neglected due to weak law enforcement and administrative irregularities in land affairs. This study emphasizes the importance of applying the principles of legality and prudence in every land rights transfer process to ensure legal certainty and justice for all parties involved in disputes.